2018
DOI: 10.1111/mec.14466
|View full text |Cite
|
Sign up to set email alerts
|

Slow evolution of sex‐biased genes in the reproductive tissue of the dioecious plant Salix viminalis

Abstract: The relative rate of evolution for sex‐biased genes has often been used as a measure of the strength of sex‐specific selection. In contrast to studies in a wide variety of animals, far less is known about the molecular evolution of sex‐biased genes in plants, particularly in dioecious angiosperms. Here, we investigate the gene expression patterns and evolution of sex‐biased genes in the dioecious plant Salix viminalis. We observe lower rates of sequence evolution for male‐biased genes expressed in the reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 115 publications
(191 reference statements)
7
55
2
Order By: Relevance
“…Although Darolti et al . () suggested that haploid selection of genes expressed in gametes may be responsible for stronger purifying selection and lower dN/dS, we found that the values of dN/dS for genes with pollen‐limited expression did not differ from those of unbiased genes. Several studies have revealed evidence for positive selection driving the evolution of sex‐biased genes in animals (Pröschel et al ., ; Baines et al ., ; Dorus et al ., ; Grath & Parsch, ; Harrison et al ., ), and two studies found evidence for positive selection in sex‐biased genes of plants.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Although Darolti et al . () suggested that haploid selection of genes expressed in gametes may be responsible for stronger purifying selection and lower dN/dS, we found that the values of dN/dS for genes with pollen‐limited expression did not differ from those of unbiased genes. Several studies have revealed evidence for positive selection driving the evolution of sex‐biased genes in animals (Pröschel et al ., ; Baines et al ., ; Dorus et al ., ; Grath & Parsch, ; Harrison et al ., ), and two studies found evidence for positive selection in sex‐biased genes of plants.…”
Section: Discussionmentioning
confidence: 48%
“…There are fewer comparisons of sex‐biased gene expression across reproductive and vegetative tissues in dioecious plants. In Silene latifolia , 17% of genes are differentially expressed in flowers, whereas < 2% are differentially expressed in leaves (Zemp et al ., ), and, in Salix viminalis , 43% of genes in catkins are differentially expressed, whereas only 0.09% of genes exhibit sex bias in leaves (Darolti et al ., ). In the current study of P. balsamifera , we found that 36% of genes expressed in catkins showed sex bias, whereas 0.003% showed sex bias in leaves.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Unlike most similar studies in other organisms, including dioecious willows (Darolti et al ., ), there were twice as many female‐biased genes compared to male‐biased genes. This result demonstrates the usefulness of studying species from many domains of life, reproductive modes, and life histories.…”
mentioning
confidence: 94%